Vibrations and waves in physics - Main, Iain G., 1932- (Cambridge University Press, 1978)
This book is designed as a text for an undergraduate course on vibrations and waves. The overall objectives of the book are to lead the student through the basic physical concepts of vibrations and waves and to demonstrate how these concepts unify a wide variety of familiar physics. This new edition contains an elementary, descriptive introduction to the important ideas of chaos. The author has also taken pains to update the applications. As with previous editions, the book contains numerous problems with hints and numerical solutions.